Recovery of Nutrients From Wastewaters Using Microalgae - Acién Fernández, Francisco Gabriel; Gómez-Serrano, Cintia; Fernández-Sevilla, José María (Frontiers in Sustainable Food Systems, 2018)
In this chapter the relevance of microalgae-based processes for the recovery of nutrients contained in wastewaters is reviewed. The fundamentals of the process are discussed from the biological and engineering standpoints and it is shown that on this type of processes the nutrient recovery capacity is mainly a function of solar radiation availability. If adequately designed and operated up to 450 tCO2, 25 tN, and 2.5 tP per hectare and per year can be fixed, producing up to 200 t/year of valuable microalgae biomass. The utilization of microalgae-based processes reduces to half the energy consumption of conventional wastewater treatment and allows recovering up to 90% of the nutrients contained into wastewater. Still the technology available (photobioreactors, harvesting, downstream) must be improved to reduce the land requirement and the hydraulic retention time, but current technology is ready to be demonstrated at large scale, so that the first initial facilities based on this technology have been recently developed. Moreover, this technology must be adapted to the different wastewater types, from sewage to manure. The major advantage of microalgae-based processes is the production of large amounts of valuable biomass, useful for the production of biofuels but much more interesting for animal feeding and agriculture uses, thus enhancing the productivity and sustainability of foods production.